The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1089/dia.2019.0018
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Closed-Loop Control Is Safe and Effective for People with Type 1 Diabetes Who Are at Moderate to High Risk for Hypoglycemia

Abstract: Background: Typically, closed-loop control (CLC) studies excluded patients with significant hypoglycemia. We evaluated the effectiveness of hybrid CLC (HCLC) versus sensor-augmented pump (SAP) in reducing hypoglycemia in this high-risk population. Methods: Forty-four subjects with type 1 diabetes, 25 women, 37-2 years old, HbA1c 7.4%-0.2% (57-1.5 mmol/mol), diabetes duration 19-2 years, on insulin pump, were enrolled at the University of Virginia (N = 33) and Stanford University (N = 11). Eligibility: increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 21 publications
2
30
0
1
Order By: Relevance
“…With the advancement of technology and closed loop systems many of the glucose metrics are improving including among them the number of hypoglycaemic events and their magnitude. Even in people at high risk for hypoglycaemia, there is currently only one Food and Drug Administration (FDA) approved system and the data were consistent with those findings 94‐96 …”
Section: Technology and Hypoglycaemiasupporting
confidence: 64%
“…With the advancement of technology and closed loop systems many of the glucose metrics are improving including among them the number of hypoglycaemic events and their magnitude. Even in people at high risk for hypoglycaemia, there is currently only one Food and Drug Administration (FDA) approved system and the data were consistent with those findings 94‐96 …”
Section: Technology and Hypoglycaemiasupporting
confidence: 64%
“…Despite these limitations, the comparisons tend to favour Diabeloop in the ways listed below. The reference time spent in the range of 3.9‐10.0 mmol/L was 23.9% (5.7 hours) longer with the Diabeloop CL system than with the OL systems. This value is in the upper range of those reported in the outpatient randomized clinical trials reviewed by Weisman et al (ie, published time‐in‐range values lie between 57% and 81%, with a −6% to 21% gain when compared with OL systems; see also Anderson et al, who reported an 18.6% gain, and Benhamou et al, who reported a 9.2% gain in a 12‐week study conducted in an ambulatory setting). Moreover, the percentage gain with the Diabeloop device is also higher than values obtained with commercially available hybrid CL devices in outpatients (14% gain found by Messer et al with the MiniMed670G, 10.3% reported by Lee et al with an enhanced version of the MiniMed670G, and 6.7% found by Biester et al with the DreaMed GlucoSitter) and in inpatients (5.7% found by Buckingham et al with a modified version of the OmniPod; see also the 10.8% gain with Tandem's Control‐IQ system as well as the clinical experience with the Medtronic 670G “hybrid” closed‐loop system presented at the American Diabetes Association's 79th Scientific Sessions).…”
Section: Discussionmentioning
confidence: 54%
“…To our knowledge, no study has investigated closed‐loop systems in patients with a very high risk of hypoglycaemia (stage 4 of CPRs, highly unstable diabetes eligible for transplant) 2 . Anderson et al investigated people with T1D who were at moderate to high risk of hypoglycaemia (patients with previous ketoacidosis or severe hypoglycaemia were excluded, and the control group was equipped with a sensor‐augmented pump system without PLGS) 22 . After 4 weeks of closed‐loop home use, the time below 70 mg/dL was 2.0% 22 compared with 0.9% in the current study.…”
Section: Discussionmentioning
confidence: 99%